ANALISIS PENGARUH PENGELUARAN PEMERINTAH DAN INVESTASI TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI JAWA TIMUR PERIODE 2015-2019 - Tikaloka Wikaningrum; Aris Soelistyo (Jurnal Ilmu Ekonomi, 2021)
This study researched the effect of government spending and investment on Gross Regional Domestic Product in East Java in 2015-2019. This research uses quantitative research. The data analysis method used was panel data regression with 30 research objects in districts/cities in East Java. This method is a combination of cross-section and time-series sourced from East Java BPS 2015-2019. The results of this study indicate that government spending variables have a significant positive effect on the Gross Regional Domestic Product. The investment variable has a significant negative effect both individually and simultaneously on the Gross Regional Domestic Product. Meanwhile, government expenditure and investment variables together have a significant effect on the Gross Regional Domestic Product in East Java.